Plugging the holes—new Canadian and US regulations to reduce upstream methane emissions. (23rd June 2019) - Ingelson, Allan
Abstract: In the USA and Canada where most of global shale oil and gas development has occurred, due to concerns about climate change the national governments have adopted new regulations to further significantly reduce national methane emissions from the upstream oil and gas industry. The 2016 US Environmental Protection Agency emissions standards and 2018 Canadian methane regulations build on decades old oil and gas conservation schemes to further reduce the volume of methane that is released from facility equipment leaks and venting. In Canada, venting methane at new oil and gas well sites is now prohibited. Operators are required to capture and use a much larger volume of natural gas than in the past. A negotiated settlement of the first US emissions reduction enforcement action was reached in April 2018. The facility operator agreed to pay a civil penalty of US 610, 000 and spend a minimum of 2 million to install new technology at its facilities to further reduce methane emissions. The creative settlement agreement contains a comprehensive set of conditions to provide for a reduction in upstream industry emissions.